N. F. S. Grundtvig: Rimbrev til Lise - Fabricius, Jørgen (Grundtvig-Studier, 1955)
N. F. S. Grundtvig: A Rhyming Letter to Lise (Aug. 12th, 1835). Edited with comments by Jørgen Fabricius. In his edition of “N. F. S. Grundtvig’s Poetical Writings” Svend Grundtvig published nine, all told, of his father’s poems to Elisabeth Christina Margrethe Blicher, to whom Grundtvig became engaged in September, 1811, and whom he married on August 12th, 1818. Five of these nine poems are, according to the information given by Svend Grundtvig, dedicatory poems which Grundtvig inscribed in books which he presented to his betrothed. Three of the other poems were composed for the occasion of “Lise’”s birthday on September 28th in the years 1815, 1825 and 1828, and, finally, one was produced for the fifth anniversary of their wedding in 1823. While this lastmentioned poem (“Hail to thee, dear mother of the boys!”) has hitherto been the only one known to have been written for an anniversary of their wedding, and a poem written in 1829 during Grundtvig’s first journey to England (“Lonely in the great swanning crowd”) has been the last of all the poems from Grundtvig’s hand known to have been written to “Lise”, the little Rhyming Letter whose text is published here will alter the position in this respect. The Rhyming Letter to Lise was written on the occasion of their wedding anniversary and — as late as 1835. — In that summer Grundtvig had rented “the end of the house” not far from “Emilie-Kilde”. “Out there I hum the old hymns to myself and the ring sweetly in my ears with the blue sea and the blue sky before my eyes”, he wrote on July 24th to his friend Gunni Busck, whose generous support not only enabled Grundtvig to set to work in earnest on “the matter of the hymns”, but also helped the family through their worst economic difficulties, which, as the Rhyming Letter clearly states, had, in particular greatly troubled Grundtvig’s wife.